Nursing care as quality management for user with tracheostomy - integrative review (Research, Society and Development, 2022)
Objective: to analyze and describe evidence of nursing care as quality management for users with tracheostomy. Methodology: integrative literature review. For the elaboration of the question, the PICO strategy was used. The search took place in 6 Latin American and Caribbean Literature in Health Sciences (LILACS), National Library of Medicine and the National Institutes of Health (Pubmed), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Database in Nursing – Brazilian Bibliography (BDENF) with a time frame of 10 years. Results: 5 studies were included that allowed discussing safe discharge, standardization of procedures, health education, multidisciplinary work and guidance on selecting the ideal tracheostomy tube, the use of communication devices, the use of daily care packages, changing of the tracheostomy, humidification, feeding time and care with cleaning the peristomal skin. Conclusion: it is necessary to consolidate evidence-based practices since there are no tracheostomy care guidelines willing to assist in the proper care of the patient with tracheostomy, seeking, in this way, to provide access to health in a comprehensive and resolute way.